2017
DOI: 10.1016/j.coisb.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Inference of cell type specific regulatory networks on mammalian lineages

Abstract: Transcriptional regulatory networks are at the core of establishing cell type specific gene expression programs. In mammalian systems, such regulatory networks are determined by multiple levels of regulation, including by transcription factors, chromatin environment, and three-dimensional organization of the genome. Recent efforts to measure diverse regulatory genomic datasets across multiple cell types and tissues offer unprecedented opportunities to examine the context-specificity and dynamics of regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 113 publications
1
18
0
Order By: Relevance
“…PBSCs. This analysis revealed that the vast majority of DHS underlying interactions between the three data-sets and those of individual patients were shared with an average level of more than 80% overlap ( Fig S8A) confirming earlier observations that the global transcriptional network of related cells is also highly related 35,36 . Sub-type-specific DHSs participating in interactions clustered within their patient group, and related groups, but not with unrelated groups (Fig S8B), confirming that the two patients were representative for those groups.…”
Section: Differential Interactions Drive Aml Subtype-specific Expresssupporting
confidence: 87%
See 1 more Smart Citation
“…PBSCs. This analysis revealed that the vast majority of DHS underlying interactions between the three data-sets and those of individual patients were shared with an average level of more than 80% overlap ( Fig S8A) confirming earlier observations that the global transcriptional network of related cells is also highly related 35,36 . Sub-type-specific DHSs participating in interactions clustered within their patient group, and related groups, but not with unrelated groups (Fig S8B), confirming that the two patients were representative for those groups.…”
Section: Differential Interactions Drive Aml Subtype-specific Expresssupporting
confidence: 87%
“…Constitutive and inducible transcription factors form regulatory circuitries and networks by interacting with their own/or other regulatory genes 35 . Cancer cells are capable of maintaining a stable regulatory network over extended periods of time, implying that the expression of each member of such a network is tightly controlled and remains in balance.…”
Section: Different Types Of Aml Are Maintained By Different Transcripmentioning
confidence: 99%
“…The majority of DHSs underlying interactions between the three data-sets and those of individual patients were shared with an average level of 80% overlap (Supplementary Fig. 8d), confirming that the global transcriptional network of related cells is highly related35,36. Sub-type-specific DHSs participating in interactions were enriched within related groups, but not within unrelated groups (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Constitutive and inducible TFs form regulatory networks by interacting with their own and/or other regulatory genes35. Cancer cells maintain a stable regulatory network, implying that the expression of each network member is tightly controlled and remains in balance.…”
Section: Resultsmentioning
confidence: 99%
“…Many techniques can be employed to improve the fidelity of a given dataset, from more effective experimental and data processing pipelines to post-processing methods for finding particular features within a dataset [1315]. Fewer analytical methods, however, focus on the dynamics of the chromatin architecture and its specificity [16]. Clustering techniques in particular may be useful in detecting functional modules of genes in Hi-C data.…”
Section: Introductionmentioning
confidence: 99%